2012
DOI: 10.1590/s1516-89132012000400013
|View full text |Cite
|
Sign up to set email alerts
|

Release of potassium from rock powder by the yeast Torulaspora globosa

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 14 publications
1
15
0
1
Order By: Relevance
“…(Sangeeth et al 2012) enhanced K solubilization by mobilizing inorganic and organic K and liberate of K from rocks and minerals. Rosa-Magri et al (2012) isolated the yeast Torulaspora globosa, from the sugarcane rhizosphere, and evaluated its capacity to solubilization of K from alkaline ultramafic rock powder and found 38 % more total K released in the medium with the yeast during a 15-day period of incubation.…”
Section: K Fixation and Releasementioning
confidence: 99%
See 1 more Smart Citation
“…(Sangeeth et al 2012) enhanced K solubilization by mobilizing inorganic and organic K and liberate of K from rocks and minerals. Rosa-Magri et al (2012) isolated the yeast Torulaspora globosa, from the sugarcane rhizosphere, and evaluated its capacity to solubilization of K from alkaline ultramafic rock powder and found 38 % more total K released in the medium with the yeast during a 15-day period of incubation.…”
Section: K Fixation and Releasementioning
confidence: 99%
“…Further, organic acids formed by KSMs can be detected by high performance liquid chromatography (HPLC) and enzymatic methods (Archana et al 2013;Zhang et al 2013). The acidification is not only mechanism of K solubilization, as the ability to decrease the pH in some cases did not associate with the capacity to solubilize mineral K (Rosa-Magri et al 2012;Zarjani et al 2013). Furthermore, the chelating ability of organic acids is important, because it has been reported that the addition of 0.05 M EDTA in to the medium has similar solubilizing result as inoculation with P. bilaii (Kucey 1988;Liu et al 2006;Sheng and He 2006).…”
Section: The Mechanisms Of K Solubilization/mobilizationmentioning
confidence: 99%
“…Rosa-Magri et al (2012) reported that a yeast species, Torulaspora globosa, released about 38 % of the total potassium from an alkaline ultramafic rock during a 15 DAI. These workers also demonstrated that the agitation during incubation (which increased oxygen availability) resulted iñ 20 % more bio-solubilization of the alkaline ultramafic rock as compared to the static culture.…”
Section: +mentioning
confidence: 99%
“…The production of organic acid can be detected through enzymatic methods and high-performance liquid chromatography (HPLC) (Archana et al 2013). However, acidification is not the only mechanism for K solubilization, because in some circumstances the decrease in pH did not affect the K solubilization (Rosa-Magri et al 2012;Keshavarz et al 2013;Meena et al 2015b). …”
Section: K Solubilization Mechanismsmentioning
confidence: 99%